2018
DOI: 10.2105/ajph.2017.304297
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Distribution of Particulate Matter Emission Sources by Race and Poverty Status

Abstract: Disparities in burden from PM-emitting facilities exist at multiple geographic scales. Disparities for Blacks are more pronounced than are disparities on the basis of poverty status. Strictly socioeconomic considerations may be insufficient to reduce PM burdens equitably across populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
186
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(206 citation statements)
references
References 23 publications
18
186
0
2
Order By: Relevance
“…Similarly Mikati et al. () used average exposures to particulate matter in 2011, assessing disproportionate exposure by race and poverty status. Abel, Salazar, and Robert () calculated emission ratios for below‐ and above‐poverty households and for whites and people of color in 1990.…”
Section: State‐level Assessment Of Environmental Inequality: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly Mikati et al. () used average exposures to particulate matter in 2011, assessing disproportionate exposure by race and poverty status. Abel, Salazar, and Robert () calculated emission ratios for below‐ and above‐poverty households and for whites and people of color in 1990.…”
Section: State‐level Assessment Of Environmental Inequality: Challengesmentioning
confidence: 99%
“…By using mean exposures, Clark, Millet, and Marshall () and Mikati et al. () failed to adequately capture differences between those in each race/income group who endure the worst pollution. Both the Abel, Salazar, and Robert () and Bullock, Ard, and Saalman (2018) teams aggregated census tract data to the county level before calculating state measures.…”
Section: State‐level Assessment Of Environmental Inequality: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 A 2018 study demonstrated that the burden of particulate emissions continued to decline sharply for all Americans, irrespective of race or income level, between 2008 and 2014. 27 And, contrary to conventional wisdom, an analysis of the economic impacts of the Clean Air Act indicates that the benefits were progressive, benefiting poorer Americans twice as much as wealthier Americans. 28 Longitudinal studies focused on youth living in southern California reveal significant gains in lung function since the mid-1990s due to improvements in air quality (even as air quality in the region continues to lag behind national standards), with the greatest gains for asthmatics and Hispanic children.…”
mentioning
confidence: 97%
“…For instance, the 2018 study that shows the continued reductions in particulate matter exposure for all Americans also demonstrates the persistence of an alarming gap in exposure levels for whites compared to non-whites. 32 But highlighting the broader legacy of environmental gains is meant to challenge any assertions that, as a column in Grist magazine recently put it, the history of environmentalism is one dominated by "large environmental organizations … mostly run by well-off white people concerned about conserving critters and our country's natural beauty, not the health and welfare of its people." 33 Not only does that statement misread the scope and consequence of American environmentalism, it also ignores the extent to which this legacy of environmental accomplishment transcends the mainstream environmental movement.…”
mentioning
confidence: 99%